PELAYANAN PUBLIK PADA PUSAT KESEHATAN MASYARAKAT DI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU TAHUN 2013-2014 - Rafni Puspita Pohan; w Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Public Services of Public Health Centers at the Sub District MarpoyanDamai in the City of Pekanbaru year 2013-2014. Purpose of this study was todetermine the Public Services in Public Health Centers at the District MarpoyanDamai in City of Pekanbaru and what are the factors that obstruct the services.This research used qualitative methods, research that provides an explanation ofdata is done through the process of preparation, presentation of data,observation, interview techniques, and Documentation. The result of thisresearch. concluded that the Public Service is still not optimal given employeehealth centers. Can be seen from the standard indicators of public servicesaccording to kepmenpan No. 63 of 2003, service procedures are difficult, longturnaround time of service, limited service products, facilities and infrastructureis not yet complete, and then the employee competence of Health Centre, who donot show a friendly attitude to patients.Keywords : Public Services, Obstruction Factors, Public Health Center (PHC)